Motivasi Ibu Muda Bergabung dengan Hijabersmom Community Aceh - Mawaddah Mawaddah (Jurnal Komunikasi Global, 2017)
This study aims to find out the motivation of youngAcehnese mothers to join the Hijabersmom Community (HmC) and the social identity created in the community. The approach used in this research is descriptive qualitative research. Primary data were collected through observation and in-depth interviews. Secondary data is collected through books, literature, brochures, websites, and other relevant documents. Informants in this study were 7 Muslim women who are members of Hijabersmom Community Aceh which includes the board and members. The results showed that the motivation of Acehnese mothers who joined in Hijabersmom Community community was the encouragement to study the science of religion and also socialize with the environment with a series of social activities as well as a means to actualize themselves through the potential and talents. While the social identity formed within this group is an exclusive group that refers to the image formation as the only community in Aceh that characterizes today's women in a fashionable and religious fashion.